An Analysis of Expressed Cheating Behaviors in Video Games. (September 2014) - Doherty, Shawn M.; Liskey, Devin; Via, Christopher M.; Frederick, Christina; Kring, Jason P.; Liu, Dahai
A series of 50 responses regarding reasons for cheating behavior in video games were provided by undergraduate students. These responses were sorted into a series of 13 categories by raters to investigate the most common reasons provided for cheating. An analysis of inter-rater agreement as well as frequency of category representation is provided. The most common outcomes were that players cheat to progress in a game as well as to gain advantage over others. The discussion compared this study's results to an existing cheating taxonomy.